2021
DOI: 10.21203/rs.3.rs-395288/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation Between BNT162b2 mRNA Covid-19 Vaccine-associated Hypermetabolic Lymphadenopathy and Humoral Immunity in Patients With Hematologic Malignancy

Abstract: Purpose: Vaccine-associated hypermetabolic lymphadenopathy (VAHL) is frequently observed on [18F]FDG PET-CT following BNT162b2 administration. Recent data suggest a prominent B-cell germinal-center (GC) response elicited by mRNA vaccines in draining lymph nodes. Thus, in this study we aimed to explore the correlation between VAHL and humoral immunity as reflected by post-vaccination serologic testing, and by comparing the incidence of VAHL between lymphoma patients treated recently with B-cell depleting therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 23 publications
(32 reference statements)
6
14
1
Order By: Relevance
“…The frequency of FDG avid LA was higher after the second vaccination compared to the first, in present study 69% vs 55% respectively, compared to 53.9% and 36.4% (9), 43.3% and 14.5% (12), respectively, in recent publications. The prevalence of LA with benign CT appearances and low-grade FDG accumulation was also similar, 77% in present study compared to 80.1% in previous study (9). This is significantly higher in comparison to axillary LA post H1V1 influenza A virus vaccination (15) which was observed in 29.3 % (13,15) and to post papilloma virus vaccination (17), probably due to the high immunogenicity of the COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The frequency of FDG avid LA was higher after the second vaccination compared to the first, in present study 69% vs 55% respectively, compared to 53.9% and 36.4% (9), 43.3% and 14.5% (12), respectively, in recent publications. The prevalence of LA with benign CT appearances and low-grade FDG accumulation was also similar, 77% in present study compared to 80.1% in previous study (9). This is significantly higher in comparison to axillary LA post H1V1 influenza A virus vaccination (15) which was observed in 29.3 % (13,15) and to post papilloma virus vaccination (17), probably due to the high immunogenicity of the COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 81%
“…Stand-alone axillary LA can be challenging in cases of lymphoma, breast cancer, melanoma, or other cutaneous malignancies. In present study we have demonstrated FDG avid LA in 59% of patients following vaccination for COVID-19 compared to 45-46 % in recent publications (9,10). The frequency of FDG avid LA was higher after the second vaccination compared to the first, in present study 69% vs 55% respectively, compared to 53.9% and 36.4% (9), 43.3% and 14.5% (12), respectively, in recent publications.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations